2001
DOI: 10.1111/j.1365-2958.2001.02325.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine levels in Bradyrhizobium japonicum membranes are critical for an efficient symbiosis with the soybean host plant

Abstract: Phosphatidylcholine (PC), the major membrane phospholipid in eukaryotes, is found in only some bacteria including members of the family Rhizobiaceae. For this reason, it has long been speculated that rhizobial PC might be required for a successful interaction of rhizobia with their legume host plants in order to allow the formation of nitrogen-fixing root nodules. A major pathway for PC formation in prokaryotes involves a threefold methylation of the precursor phosphatidylethanolamine (PE). Here, we report on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 50 publications
4
97
0
Order By: Relevance
“…A similar conclusion was drawn from recent studies performed by Wilderman et al (2002). Earlier work on the methylation pathway of PC biosynthesis in Bradyrhizobium japonicum (Minder et al, 2001) suggested that besides a phospholipid N-methyltransferase (PmtA) catalysing efficiently the first methylation, and therefore the formation of MMPE, another phospholipid methyltransferase (PmtX) activity must exist in this organism which efficiently performs the second and third methylation required for PC formation via the methylation pathway. In the Bradyrhizobium japonicum genome sequence (Kaneko et al, 2002), two homologues (Bjap ORF1 and Bjap ORF2) of the rhodobacterial PmtA exist that could qualify as candidates for PmtX.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…A similar conclusion was drawn from recent studies performed by Wilderman et al (2002). Earlier work on the methylation pathway of PC biosynthesis in Bradyrhizobium japonicum (Minder et al, 2001) suggested that besides a phospholipid N-methyltransferase (PmtA) catalysing efficiently the first methylation, and therefore the formation of MMPE, another phospholipid methyltransferase (PmtX) activity must exist in this organism which efficiently performs the second and third methylation required for PC formation via the methylation pathway. In the Bradyrhizobium japonicum genome sequence (Kaneko et al, 2002), two homologues (Bjap ORF1 and Bjap ORF2) of the rhodobacterial PmtA exist that could qualify as candidates for PmtX.…”
Section: Discussionsupporting
confidence: 50%
“…Studies with Sinorhizobium meliloti demonstrated that PC can be synthesized via two different routes, the PMT (de Rudder et al, 2000) pathway, represented by phospholipid Nmethyltransferase (PmtA) enzymes, or the PCS (de Rudder et al, 1999;Sohlenkamp et al, 2000) pathway. In recent years, numerous homologues of PmtA or Pcs have been described, but only a few have been evaluated experimentally (Hanada et al, 2001;Minder et al, 2001;Wilderman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of respiratory quinones and polar lipids have been suggested for characterization for prokaryotes (Tindall et al, 2010), but there are few publications on taxonomy of rhizobia (Choma & Komaniecka, 2003;Miller et al, 1990;Minder et al, 2001;Orgambide et al, 1993). The respiratory quinones for CCBAU 15774 T , B. liaoningense USDA 3622 T , B. yuanmingense CCBAU 10071 T , B. betae LMG 21987 T and B. japonicum USDA 6 T were analysed by HPLC as described by Lee et al (2001).…”
mentioning
confidence: 99%